The Alien Protocol: steps towards a communism of the strange - Neyrat, Frédéric ((Des)troços: revista de pensamento radical, 2021)
“The Alien Protocol” is neither a manifesto, nor a program, but a series of metaphysical and metapolitical formulas on how the category of alien could found a communism 1) neither centered on the reappropriation of an essence or the delimitation of a territory on which to install a strictly local way of life, 2) nor on the belief of a way out of geo-capitalism through the intensification of its global logic: an alien communism refuses a retreat to territorial identity as much as the acceleration of techno-capitalist alienation.